Expanding phenotype of MED13-associated syndrome presenting novel de novo missense variant in a patient with multiple congenital anomalies - Ekaterina Tolmacheva; Anna S. Bolshakova; Jekaterina Shubina; Margarita S. Rogacheva; Alexey N. Ekimov; Julia L. Podurovskaya; Artem A. Burov; Denis V. Rebrikov; Vladimir G. Bychenko; Dmitry Yu. Trofimov; Gennady T. Sukhikh (BMC, 2024)
Abstract Background Whole exome sequencing allows rapid identification of causative single nucleotide variants and short insertions/deletions in children with congenital anomalies and/or intellectual disability, which aids in accurate diagnosis, prognosis, appropriate therapeutic interventions, and family counselling. Recently, de novo variants in the MED13 gene were described in patients with an intellectual developmental disorder that included global developmental delay, mild congenital heart anomalies, and hearing and vision problems in some patients. Results Here we describe an infant who carried a de novo p.Pro835Ser missense variant in the MED13 gene, according to whole exome trio sequencing. He presented with congenital heart anomalies, dysmorphic features, hydrocephalic changes, hypoplastic corpus callosum, bilateral optic nerve atrophy, optic chiasm atrophy, brain stem atrophy, and overall a more severe condition compared to previously described patients. Conclusions Therefore, we propose to expand the MED13-associated phenotype to include severe complications that could end up with multiple organ failure and neonatal death.